Paddy farmers' knowledge, perception, and satisfaction on the use of Information and Communication Technology (ICT) tools in Nepal - Udit Prakash Sigdel; Kailash Nath Pyakuryal; Durga Devkota; Gana Pati Ojha (Turkish Journal of Agriculture: Food Science and Technology)
Information and communication technology (ICT) tools such as radio, television, mobile phone, the internet, computers are gaining momentum in the development discourse of the agriculture sector in Nepal. In agriculture extension, ICT tools fill the void that traditional agriculture extension cannot address. So, this study aimed at assessing the paddy farmers' knowledge, perception, and satisfaction on ICT tools in Jhapa, Kapilbastu, and Kailai districts following a multistage purposive sampling method. A survey research design was used for the study. Pretested semi-structured interview schedule was employed to randomly selected 390 sample respondents. Descriptive statistics along with the appropriately developed scales were used in the data analysis. The findings revealed that respondents were moderately aware (0.44) of the significant roles of ICT tools. Respondents do have more knowledge on the radio (0.87), TV (0.85), and mobile phones (0.76), whereas the majority possess TV (94%), radio (93%), and mobile phones (88%) among ICT tools. Farmers from Bardiya were more aware of the roles of ICT as compared to other study districts. Likewise, Radio and TV were the primary ICT tools used for agriculture-related information. Respondents had high skills in using radio and TV for information but poor skills in using the computer in all study districts. Most of the respondents positively perceived (0.14) ICT tools and were satisfied (0.23) with them, but their use was limited to radio, TV, and mobile phones. In addition, farmers of Kapilbastu districts were less satisfied with the use of ICT tools as compared to other study districts.